Hippocampal transcriptome profiling reveals status epilepticus-induced early changes in gene expression mainly implicating in neuroinflammation and immune responses linked to microglial dysfunction - Hui-Ling Tang; Yu Min; Yue-Sheng Long (PLoS ONE, 2026)
Status epilepticus (SE) is a severe type of epileptic seizure and induces molecular and cellular changes in the brain tissues which contribute to neuron injury. Here we used RNA sequencing to determine changes in hippocampal gene expression in pilocarpine-induced SE mice at 3-hour (SE-3h) and 24-hour (SE-24h) time points, a crucial stage of SE-induced brain acute damage. A total of 366 differentially expressed genes (DEGs) were identified from the SE-3h hippocampus and 570 DEGs from the SE-24h hippocampus, and most of them were up-regulated upon SE induction. Bioinformatical analyses showed that, compared to SE-3h up-regulated genes with poor scores in functional and pathway enrichment, the SE-24h up-regulated genes were predominantly enriched in inflammatory and immune response, positive regulation of response to external stimuli and inflammatory response (GO function), and Microglia pathogen phagocytosis pathway and Tyrobp causal network in microglia (WikiPathway). Specifically, a subset of DEGs such as Tyrobp , C1qc , Itgb2 , Ncf2 , and Nckap1l involved in the two pathways are present in the inflammatory and immune cascades. Therefore, this study delineates early altered transcriptional profiles in the hippocampus after SE, and highlights up-regulation of a subset of genes might be involved in the activation of microglia-mediated inflammatory and immune responses linked to the early pathogenesis of SE-induced brain injury.